Perception and acceptance toward green practice in controlling nettle caterpillar among oil palm smallholder / Mohd Nor Hafizul Mohamad Zaki - Mohamad Zaki, Mohd Nor Hafizul (Faculty of Plantation and Agrotechnology, 2017)
In Malaysia, oil palm or it sscientific name Elaeis guineensisis considered to be a major crop that provides a high economic income to our country, but the infection from the pest and disease can cause big problem toward soil palm plantation. When the pest and disease attack the oil palm field, it can cause losses of oil palm yield and the productivity. The problem of this study is the infection of the nettle caterpillar in oil palm plantation which can reduce the yield of the oil palm. This study was conducted to identify the most influence factor that affect perception and acceptance towards green practices among oil palm smallholder at Dungun, Terengganu. The survey method was applied in this study which data collection and questionnaire were distributed to 95 respondents from 120 population of oil palm smallholders in Dungun, Terengganu. The result were interpreted using hypothesis testing, descriptive analysis, Spearman correlation and regression by using Statistical Package for Science Social (SPSS). Based on correlation analysis result, it show that all in dependent variable has strong relationship correlation ( r= 0.50-0.69, p<0.05) with dependent variable.From regression analysis, it was identified that environmental friendly is the most influence factor that effect the perception and acceptance toward green practice in controlling the infection of nettle caterpillar among oil palm smallholders( beta value =0.361, p<0.05). The results obtained in this research could be reference for future research in this field. In conclusion, government are responsible to educate and take action toward smallholder in spread the information about the green practice as knowledge to the oil palm smallholders to apply about this concept in their oil palm field.